Framing sexual and domestic violence through language - Klein, Renate (Palgrave Macmillan, 2013)
"Violence against women is a growing problem. With examples from Denmark, France, Poland, Switzerland, the United Kingdom, and the United States, the contributors to this volume explore how violence is framed through language and what this means for research and policy. They look at how metaphors in police homicide reports obscure domestic violence, how abstract language conveys stereotypes without anybody noticing, and how Western authorities have struggled to understand crimes in the name of honor. Language shapes responses to abuse and approaches to perpetrators and interfaces with national debates about gender, violence, and social change." --